Pola Komunikasi Dakwah Bil Hal Muhammadiyah pada Masyarakat Agraris - Euis Evi Puspitasari; Utan Sahiro Ritonga (CHANNEL: Jurnal Komunikasi, 2020)
Not only oral (tabligh, oral, and written) da'wah that can be done to touch certain communities such as the farming community, but also the planned dakwah bil hal (da'wah with action).Â  Dakwah bil hal Â  requires a communication pattern so that various activities planned in the program can be carried out following the expectations of the parties involved. By using qualitative descriptive methods and interactive model data analysis techniques. It is known that there are four communication patterns implemented by Muhammadiyah administrators in Bandung Regency including interpersonal communication patterns, group communication, public communication, and mass communication. Interpersonal communication patterns and group communication patterns are the most effective communication used in the implementation of preaching when it comes to Muhammadiyah.